CREATIVITY OF DRIVING TEACHERS IN DEVELOPING STUDENTS' SOCIAL-EMOTIONAL COMPETENCE (SEC) ON AN INDEPENDENT LEARNING CURRICULUM - Cahyati, Cucu; Ahmadin, Ahmadin; Ramadhan , Syahru (Waniambey: Journal of Islamic Education, 2024)
This research discusses the creativity of the driving teacher in developing students' social and emotional competencies in the Merdeka curriculum at State Primary school 21 Tolomundu, Bima City. The mobilising teacher has an important role in improving the quality of teaching and learning, as well as in developing students' character and creativity. In the Merdeka curriculum, mobilising teachers are expected to act as agents of change who facilitate the exchange of ideas, provide support for fellow teachers, and build an inclusive and supportive learning environment. In this research, mobilising teachers in Bima are equipped with the skills and knowledge needed to lead change in teaching and learning practices. through this research, the author uses a type of qualitative research with a descriptive approach, which aims to reveal symptoms in a holistic-contextual manner through data collection from a natural setting by utilising the author as a key instrument. The key information in this research is the school principal, teacher activists and students at the State Primary school 21 Tolomundu, Bima City. To collect data the author conducted observations, interviews and documentation.  After collecting the data the author directly analyses the data. Based on the results of the study, it shows that increased awareness and understanding of the importance of social and emotional competence, improved student skills in managing emotions, communicating, and working together, changes in school culture towards a more inclusive environment, and improved teaching quality and student engagement. The impact is not only felt at school, but also has the ability to improve the quality of life of students more broadly